(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Energy efficiency plays a critical yet underutilised role in expanding access to clean, affordable, and reliable energy services in developing regions. In Sub‑Saharan Africa, energy policy interventions have historically prioritised supply expansion, often overlooking the significant potential of demand‑side energy efficiency measures. This paper evaluates the economic and systemic effectiveness of reducing energy demand as a strategy for improving energy access while enhancing sustainability. It examines key technical, financial, institutional, and informational barriers that constrain the adoption of energy‑efficient technologies and practices across the region. The analysis demonstrates that targeted policy interventions including regulatory frameworks, financial incentives, and capacity‑building initiatives, can accelerate the uptake of energy‑efficient buildings, appliances, and industrial systems. Strengthening incentives for households, utilities, and industries can support long‑term investments in cost‑effective energy efficiency measures. The study concludes that integrating energy efficiency into national energy access strategies represents a scalable and economically sound pathway toward achieving universal energy access and sustainable development in Sub‑Saharan Africa.